Respuesta :

Answer:

Option (2) is correct.

We can write [tex]x^2-16x+64=-8[/tex] as [tex](x-8)^2=-8[/tex]

Step-by-step explanation:

Consider the given equation [tex]x^2-16x+64=-8[/tex]

We have to rewrite it in form of identity [tex](a-b)^2[/tex]

We know  [tex](a-b)^2=a^2+b^2-2ab[/tex]

Consider the left side of the given equation,

[tex]x^2-16x+64[/tex]

this can be written in form of [tex](a-b)^2=a^2+b^2-2ab[/tex]

Here a = x , b = 8 , -2ab= -2 × x ×8

Then left side becomes,

[tex]x^2-16x+64=(x-8)^2[/tex]

Thus , we can write [tex]x^2-16x+64=-8[/tex] as [tex](x-8)^2=-8[/tex]

Thus, option (2) is correct.

Answer:

B

Step-by-step explanation:

ACCESS MORE